Spatial analysis of the main determinants and indicators associated with diarrhea mortality in the state of Ceará in the past ten years (Research, Society and Development, 2022)
Objective: To carry out a spatial analysis of the main determinants and indicators associated with mortality from diarrhea in the state of Ceará in the last ten years. Methodology: Ecological study, using the Mortality Information System as a data source, considering death from diarrheal disease during the period from 2008 to 2017. For spatial analysis, a map of the mortality rate of each municipality was created and these rates were smoothed using the local empirical Bayesian method. The Local Index of Spatial Association autocorrelation was evaluated by the Local Moran Index. The calculations of the raw and smoothed rate as well as the Moran scattering index and its significance were performed by the TerraView 4.2.2 software. All maps were produced in QGIS 2.4.17 software. Results: In the spatial autocorrelation analysis, the Global Moran Index was equal to 0.14 with p=0.02, indicating a positive spatial autocorrelation. The temporal evolution of the diarrhea mortality rate between the years 2008 and 2017 in the state of Ceará is evidenced. There was a decrease in cases in 2012 and a considerable increase in mortality from diarrheal diseases in 2017. It is inferred that in the years 2014, 2015, 2016 and 2017 there was an increase in cases, being prevalent in the municipalities of Barroquinhas, Frecheiras, Mucambo, Pacujá and Fortim; Amontada; Sobral; Senador Pompeu e Groaíras, respectively. Conclusion: Infant mortality in Ceará caused by diarrhea suffered declines and rises in the analyzed period, not observing a constancy of this process, still presenting important differences between the microregions under study.